The Effect of Painting Activities Using Water Hyacinth Fiber Media on Learning Interest and Creativity of Fifth-Grade Students at SD Negeri Wonosari Baru Cluster 2 Kapanewon Wonosari - Retno Purwaningrum; Banu Setyo Adi (Publikasi Pendidikan, 2026)
This study examined the effect of painting activities using water hyacinth fiber as a natural medium on learning interest and creativity of fifth-grade elementary school students in visual arts. A quasi-experimental design with a nonequivalent control group was conducted at SD Negeri Wonosari Baru, involving an experimental class of 28 students and a control class of 27 students. Data were collected through validated and reliable questionnaires measuring learning interest and creativity, with reliability coefficients of 0.841 and 0.950. Data analysis employed independent sample t-tests, paired sample t-tests, and MANOVA. The results indicate that painting activities using water hyacinth fiber significantly improved students’ learning interest and creativity. MANOVA analysis showed a strong overall effect, with a Wilks’ Lambda value of 0.192 and a Partial Eta Squared of 0.808 (p < 0.001). Univariate tests revealed significant effects on learning interest (p = 0.001, η² = 0.194) and creativity (p = 0.000, η² = 0.780). These findings highlight the impact of integrating local and environmentally friendly materials into art instruction. The use of water hyacinth fiber provides meaningful learning experiences that enhance engagement and creative expression in elementary visual arts education.